Applying RFID technology in the retail industry – benefits and concerns from the consumer’s perspective - Ádám Novotny; Lóránt Dávid; Hajnalka Csáfor (Amfiteatru Economic)
This paper discusses the benefits and costs of RFID (Radio Frequency Identification) technology in the retail sector. RFID is an enabling technology for the Internet of Things (IoT) concept, which constitutes a new vision of the Internet as a medium and forum that expands into our everyday lives and connects us virtually to all of the objects that surround us. This paper gives a balanced view of RFID in retailing by showing its current and potential benefits and costs, in particular from the consumer’s perspective. The authors also present the findings of a survey that examined the attitudes of Hungarian consumers towards the potential threats of RFID, and conclude that these attitudes are part of a larger psychological construct, which embraces opinions and attitudes towards new information and communications technologies in general. Significant relationships between consumer demography and attitudes towards RFID applications were also revealed. The paper suggests a solution to the privacy problem of current RFID applications, which has been elaborated by researchers of the IoT Research Institute at the Eszterházy Károly College in Hungary: if RFID technology were integrated with NFC-enabled mobile phones that included a user interface, consumers would be able to gain control over radio frequency communication.